Seni dalam Proses Pembukuan berdasarkan Etika Profesi Akuntansi: (Kasus Pencatatan Laporan Keuangan PT DNN Mojokerto) - Siti Robbana (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2023)
Accounting is an activity of assessment, measurement to decision making. Reporting in accounting is carried out by an accountant by recording according to the data or information obtained. Accountant is one of the important professions in the business world because it is related to finance, therefore it is mandatory for an accountant to apply the existing ethics of the accounting profession. The purpose of this study was to determine violations of the ethics of the accountant profession at PT DNN Mojokerto in recording financial statements. This research uses a descriptive method with a qualitative approach using data from literature studies and data from the company with the approval of the company director, so that the company becomes better for the future progress of the company. The results of this study indicate that PT DNN Mojokerto does not understand about recording financial statements, both from recording, in accordance with applicable financial accounting standards, framing, reporting, and analyzing data.